Evaluation of a BICROS System with a Directional Microphone in the Receiver and Transmitter. - Valente, Michael; Oeding, Kristi (Journal of the American Academy of Audiology)
Background: The bilateral contralateral routing of signals (BICROS) system has provided limited benefit for speech recognition in noise for patients with asymmetric sensorineural hearing loss, even when an automatic adaptive multichannel directional microphone (DM) is in the receiver (Rx) and an omnidirectional microphone (OM) is in the transmitter (Tx). A recent BICROS system was introduced that can be programmed with a DM in the Rx and an OM or a DM in the Tx. Purpose: To examine if significant differences in sentence recognition in noise and subjective preferences are present between an OM and an adaptive broadband DM programmed in the Tx of a BICROS system with an automatic adaptive multichannel DM programmed in the Rx. Research Design: A randomized crossover single-blind design was used to assess differences between the OM and DM programmed in the Tx. Study Sample: Eighteen adult experienced BICROS system users were recruited. Data Collection and Analysis: The BICROS system was fit using real-ear insertion gain measures. The Tx was programmed with an OM and a DM and the Rx was always programmed with an automatic adaptive multichannel DM. The order of microphone condition in the Tx was counterbalanced. Participants acclimatized to the BICROS system for 4 weeks and returned and completed the Abbreviated Profile of Hearing Aid Benefit (APHAB) for the respective microphone condition. The Tx was then programmed with the other microphone condition and participants acclimatized for another four weeks. At the final visit, the APHAB was completed for the respective microphone condition. After eight weeks of acclimatization, Hearing in Noise Test sentences were presented in the R-Space™ system with the Tx in either the OM or DM condition for three listening conditions: (1) speech from 90° to the Rx and noise from 0°, 90°, and 180° to the Tx (Sp Rx/N Tx), (2) speech from 90° to the Tx and noise from 0°, 90°, and 180° to the Rx (Sp Tx/N Rx), and (3) speech from 0° and noise from eight surrounding loudspeakers separated by 45° (diffuse). Results: A two-factor repeated measures analysis of variance revealed no significant differences between the OM and DM microphone conditions for Sp Rx/N Tx listening condition. A significant mean disadvantage of 1.9 dB (p < 0.01) was revealed for the DM compared to the OM for Sp Tx/N Rx listening condition and a mean advantage of 2.6 dB (p < 0.001) for the DM compared to the OM in a diffuse listening condition. There were no significant differences in the APHAB aided problem and resulting benefit scores between the OM and DM for the following subscales: ease of communication, background noise, reverberation, and aversiveness of sounds.Conclusions: No significant differences were revealed between OM and DM for Sp Rx/N Tx. The DM performed significantly poorer than OM for the Sp Tx/N Rx listening condition. Results revealed significant benefit for the DM compared to OM for the diffuse listening condition. No significant differences were revealed between the OM and DM on the APHAB.